EVAR: Benefits of CEUS for monitoring stent-graft status. Issue 9 (September 2015) - Cantisani, Vito; Grazhdani, Hektor; Clevert, Dirk-André; Iezzi, Roberto; Aiani, Luca; Martegani, Alberto; Fanelli, Fabrizio; Di Marzo, Luca; Wlderk, Andrea; Cirelli, Carlo; Catalano, Carlo; Di Leo, Nicola; et al.
Highlights: In the last two decades several studies have shown the role of contrast enhanced ultrasound [CEUS] in post-EVAR surveillance, with very good diagnostic performance, absence of renal impairment, and no radiation, accompanied by low costs, in comparison with CTA. In numerous prospective studies and meta-analyses the detection and characterization of endoleaks with CEUS is comparable to that of CTA imaging. Nowadays in the EVAR surveillance novel strategies which involve CEUS with a central role, are suggested by several authors and applied in many institutions. CEUS technique, findings, diagnostic accuracy, and its role in the follow up program are discussed in this review article. Abstract: Endo vascular aortic repair [EVAR] is performed with low peri-operative morbidity and mortality rate and short hospital stay. However, EVAR needs a close and lifelong imagining surveillance for a timely detection of possible complications including endoleaks, graft migration, fractures, and enlargement of aneurysm sac size with eventual rupture. Contrast enhanced computed tomography [CTA] is actually considered the gold-standard in EVAR follow-up, but it is accompanied with radiation burden and renal injury due to the use of contrast media. In the last two decades several studies have shown the role of contrast enhanced ultrasound [CEUS] in post-EVAR surveillance, with very good diagnostic performance, absence of renal impairment, and no radiation, accompanied by low costs, in comparison with CTA. In numerous prospective studies and meta-analyses the detection and characterization of endoleaks with CEUS is comparable to that of CTA imaging. Nowadays, in the EVAR surveillance novel strategies which involve CEUS with a central role, are suggested by several authors and applied in many institutions. In this review article we will present a comprehensive overview and analyses of the literature on the CEUS state-of-art imagining of EVAR follow-up, with its technique, findings, diagnostic accuracy, and its role in the follow up program.